Maternal Risk Factors Associated with Hypospadias - Bindu S1, Guntaka A K1, Patil S M1, Neelgund S E2, Hiremath M B1, Nerli R B1,2*, (Recent Research in Science and Technology, 2010)
Abstract Introduction: Epidemiological studies have elucidated maternal and fetal factors that are associated with an increased risk of hypospadias .This study examined the association of hypospadias risk with several maternal reproductive and demographic characteristics: age, parity, body mass index (BMI), nausea and vomiting of pregnancy, fertility treatments , education and diet . Materials and Methods: Mothers of children with hypospadias were invited to participate in this case control study. Participating mothers completed a self administered questionnaire or a social worker administered/assisted questionnaire. Mothers of age matched children without hypospadias acted as controls and they too similarly completed the same questionnaire. Results: The risk factors associated with hypospadias were maternal age, primiparity , previous fertility treatment and nausea and vomiting of pregnancy . Conclusions: Increased maternal age, primiparity and previous fertility treatments in mothers are associated with an increased risk of hypospadias in male offsprings. Keywords: Hypospadias, Maternal age, Parity, Fertility, Maternal education, Nausea and vomiting